Resistance Modulation Action, Time-Kill Kinetics Assay, and Inhibition of Biofilm Formation Effects of Plumbagin from Plumbago zeylanica Linn - Emmanuel B. A. Adusei; Reimmel K. Adosraku; James Oppong-Kyekyeku; Cedric D. K. Amengor; Yakubu Jibira (Journal of Tropical Medicine)
Antimicrobial resistance (AMR) is a threat to the prevention and treatment of the increasing range of infectious diseases. There is therefore the need for renewed efforts into antimicrobial discovery and development to combat the menace. The antimicrobial activity of plumbagin isolated from roots of Plumbago zeylanica against selected organisms was evaluated for resistance modulation antimicrobial assay, time-kill kinetics assay, and inhibition of biofilm formation. The minimum inhibitory concentrations (MICs) of plumbagin and standard drugs were determined via the broth microdilution method to be 0.5 to 8 μg/mL and 0.25–128 μg/mL, respectively. In the resistance modulation study, MICs of the standard drugs were redetermined in the presence of subinhibitory concentration of plumbagin (4 μg/mL), and plumbagin was found to either potentiate or reduce the activities of these standard drugs with the highest potentiation recorded up to 12-folds for ketoconazole against Candida albicans. Plumbagin was found to be bacteriostatic and fungistatic from the time-kill kinetics study. Plumbagin demonstrated strong inhibition of biofilm formation activity at concentrations of 128, 64, and 32 μg/mL against the test microorganisms compared with ciprofloxacin. Plumbagin has been proved through this study to be a suitable lead compound in antimicrobial resistance drug development.